Investigation into the neural correlates of emotional augmentation of clinical pain. - Schweinhardt, P; Kalk, N; Wartolowska, K; Chessell, I; Wordsworth, P; Tracey, I (2008)
Although depressive mood is an important psychological determinate of chronic pain, the neural circuitry that mediates its influence on the pain experience is largely unknown. We used functional magnetic resonance imaging (FMRI) to investigate the neurophysiological interactions between depressive symptoms and disease-relevant pain in rheumatoid arthritis (RA) patients. RA is associated with chronic joint pain and swelling, but peripheral joint pathology often does not fully explain the amount of pain a patient experiences. We investigated the neural circuitry that relates joint pain and depressive symptoms and contrasted this with experimental heat pain. We hypothesized that (1) depressive symptoms influence the cerebral processing of provoked joint pain in RA, and (2) the interaction of depressive symptoms with pain processing contributes to the pain RA patients experience on a daily basis. Twenty patients underwent whole brain FMRI during which disease-relevant joint pain was provoked. Depressive symptoms were assessed using the Beck Depression Inventory (BDI). The tender-to-swollen joint ratio (T/S) was assessed as one component of the patients' clinical pain. BDI scores correlated significantly with T/S and medial prefrontal cortex (MPFC) activation during provoked joint pain. The association between BDI scores and T/S was partly mediated by the MPFC activation. Furthermore, the MPFC activation co-varied significantly with the FMRI signal in limbic areas and in areas that process self-relevant information. These results suggest that the MPFC may play an important role in mediating the relationship between depressive symptoms and clinical pain severity in RA, possibly by engaging brain areas important for affective and self-relevant processing.